2021
DOI: 10.3390/ijms22083978
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin-Stimulated LAD2 Human Mast Cell Line Is a Potent Cellular Adjuvant for the Maturation of Monocyte-Derived Dendritic Cells for Adoptive Cellular Immunotherapy

Abstract: The preparation of dendritic cells (DCs) for adoptive cellular immunotherapy (ACI) requires the maturation of ex vivo-produced immature(i) DCs. This maturation ensures that the antigen presentation triggers an immune response towards the antigen-expressing cells. Although there is a large number of maturation agents capable of inducing strong DC maturation, there is still only a very limited number of these agents approved for use in the production of DCs for ACI. In seeking novel DC maturation agents, we used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Furthermore, MCs may play roles in other immune-related domains, such as mediating allograft tolerance [20] and potentially serving pivotal roles in anticancer immunity [21]. The intricate interplay between MCs and DCs significantly contributes to our understanding of tumor immune responses and development of novel immunotherapeutic strategies [15,16,[22][23][24][25]. Consequently, future research should prioritize unraveling the detailed mechanisms underlying these interactions to maximize their potential in tumor immunotherapy.…”
Section: Interaction Between Mcs and Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MCs may play roles in other immune-related domains, such as mediating allograft tolerance [20] and potentially serving pivotal roles in anticancer immunity [21]. The intricate interplay between MCs and DCs significantly contributes to our understanding of tumor immune responses and development of novel immunotherapeutic strategies [15,16,[22][23][24][25]. Consequently, future research should prioritize unraveling the detailed mechanisms underlying these interactions to maximize their potential in tumor immunotherapy.…”
Section: Interaction Between Mcs and Immune Cellsmentioning
confidence: 99%
“…[ [15][16][17][18][19][20][21][22][23][24][25] • MCs and T Cells MCs and their complex interactions within cellular networks significantly impact T cell activity.…”
Section: Mcs and T Cellsmentioning
confidence: 99%
“…In this regard, the interaction of MCs with DCs may come with an advantage in the ex vivo preparation of DCs. In our previous work, we found that a stimulated human LAD2 MC line could be a highly potent cellular adjuvant for the maturation of ex-vivo-produced human-monocyte-derived DCs for ACT [ 157 ]. This high adjuvant potency was conditioned by previous MC stimulation with thapsigargin, an inhibitor of sarco/endoplasmic reticulum Ca 2+ -ATPases (SERCA) [ 158 , 159 ], which induces a strong mobilization of intracellular calcium followed by fast and extensive degranulation of LAD2 MCs [ 160 ].…”
Section: Mc/dc Interplay As the Cellular Immune Checkpoint For Cancer...mentioning
confidence: 99%
“…Such previously stimulated and rinsed LAD2 MCs were, unlike their non-stimulated or FcεRI-stimulated counterparts, able to mature monocyte-derived DCs, which were even refractory to the maturation with polyinosinic:polycytidylic acid (poly I:C), a toll-like receptor-3 agonist often used for the production of matured DCs for ACT-based cancer cellular immunotherapy [ 154 , 155 ]. Moreover, the study showed that the adjuvant effect was still notable even when the MC:DC ratio was 1:150 [ 157 ]. This maturation efficiency indicated that a very small number of MCs can promote DC maturation.…”
Section: Mc/dc Interplay As the Cellular Immune Checkpoint For Cancer...mentioning
confidence: 99%
“…Considerable attention has been given to the role of MCs in regulating T-cell function, either directly or indirectly, through actions on dendritic cells (DCs). In this issue, Taborska et al [ 2 ] show that differentially stimulated MCs could be novel and highly potent cellular adjuvants for the maturation of DCs, and this ability opens a new avenue to use activated MCs for adoptive cellular immunotherapy. This procedure requires the maturation of ex vivo-produced immature DCs to mount an immune response against the antigen-expressing cells.…”
mentioning
confidence: 99%